HIV-1-Specific CAR-T Cells With Cell-Intrinsic PD-1 Checkpoint Blockade Enhance Anti-HIV Efficacy in vivo - Jiang, Zhengtao; Liang, Huitong; Pan, Hanyu; Liang, Yue; Wang, Hua; Yang, Xinyi; Lu, Panpan; Zhang, Xiao; Yang, Jinlong; Zhang, Dengji; Shen, Xiaoting; Wang, Jing; et al. (Frontiers in Microbiology, 2021)
Adoptive cellular immunotherapy therapy using broadly neutralizing antibody-based chimeric antigen receptor-T cells (bNAb-based CAR-T) has shown great potency and safety for the functional cure of HIV. The efficacy of bNAb-based CAR-T cells could be compromised by adaptive resistance during HIV chronic infection according to the phenomenon that cellular exhaustion was observed in endogenous cytotoxic T-lymphocytes (CTLs) along with upregulated expression of PD-1. Here, we created HIV-specific CAR-T cells using human peripheral blood mononuclear cells (PBMCs) and a 3BNC117-DNR CAR (3BD CAR) construct that enables the expression of PD-1 dominant negative receptor (DNR) and the single-chain variable fragment of the HIV-1-specific broadly neutralizing antibody 3BNC117 to target native HIV envelope glycoprotein (Env). Compared with HIV CAR expression alone, 3BD CAR-T cells displayed potent lytic and functional responses to Env-expressing cell lines and HIV-infected CD4⁺ T cells. Moreover, 3BD CAR-T cells can kill HIV-latently-infected cell lines, which are reactivated by the secretory cytokines of effector cells followed by contact with initial HIV-expressing fraction. Furthermore, bioluminescence imaging indicated that 3BD CAR-T cells displayed superior anti-HIV function in an HIV NCG mouse model of transplanting Env+/PD-L1+ cells (LEL6). These studies suggested that our proposed combinational strategy of HIV CAR-T therapy with PD-1 blockade therapy is feasible and potent, making it a promising therapeutic candidate for HIV functional cure.